2022
DOI: 10.1186/s12891-022-05708-9
|View full text |Cite
|
Sign up to set email alerts
|

‘I was young, I wanted to return to sport, and re-ruptured my ACL’ – young active female patients’ voices on the experience of sustaining an ACL re-rupture, a qualitative study

Abstract: Background Despite anterior cruciate ligament (ACL) re-ruptures being common, research on patient experiences after knee trauma has primarily focused on the time after primary ACL reconstruction. Integrating qualitative research and patient experiences can facilitate researchers and clinicians in understanding the burden of an ACL re-rupture. The aim of the study was to explore the experiences of an ACL re-rupture journey in young active females aiming to return to knee-strenuous sports after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
(49 reference statements)
1
12
0
1
Order By: Relevance
“…Patients' descriptions of feelings include: burden, worry, frustration, hopelessness, devastation, and isolation. 23,30,36,52,68 Mental health conditions, such as anxiety and depression, may increase in severity in response to injury and be detrimental to outcomes. 46 Schaffer et al 58 observed outcomes of patients stratified into 3 cohorts: clinical diagnosis of depression, situational depression, and no depression.…”
Section: Impact Of Injury Experiencementioning
confidence: 99%
See 3 more Smart Citations
“…Patients' descriptions of feelings include: burden, worry, frustration, hopelessness, devastation, and isolation. 23,30,36,52,68 Mental health conditions, such as anxiety and depression, may increase in severity in response to injury and be detrimental to outcomes. 46 Schaffer et al 58 observed outcomes of patients stratified into 3 cohorts: clinical diagnosis of depression, situational depression, and no depression.…”
Section: Impact Of Injury Experiencementioning
confidence: 99%
“…55,66 However, on-field and competitive rehabilitation activities should be practiced with caution; some patients find the experience demotivating when unable to contribute or keep up. 52,55 Interactions with coaches also contribute heavily. The authority and confidence they hold gives them the opportunity to encourage and motivate athletes, especially when they are involved in recovery and RTS decisions.…”
Section: Impact Of Injury Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…In diesem Zusammenhang ist von großer Bedeutung, dass viele Sportler ihr Selbstwertgefühl in einem hohen Maß durch die Partizipation und die Anerkennung innerhalb des Sports erfahren. Eine Sportkarenz geht daher fast immer mit einer Herabsetzung der eigenen Wertschätzung bis hin zur Zerstörung der eigenen Identität einher [36] [61].…”
Section: Psychologische Reaktion Nach Einem Traumaunclassified